2004
DOI: 10.1187/cbe.04-06-0041
|View full text |Cite
|
Sign up to set email alerts
|

Students' Studying and Approaches to Learning in Introductory Biology

Abstract: This exploratory study was conducted in an introductory biology course to determine 1) how students used the large lecture environment to create their own learning tasks during studying and 2) whether meaningful learning resulted from the students' efforts. Academic task research from the K-12 education literature and student approaches to learning research from the postsecondary education literature provided the theoretical framework for the mixed methods study. The subject topic was cell division. Findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…In this model, a task is demonstrated to be important with a reward of in-class validation, emphasizing the learning process and the value of sharing scientific ideas rather than correctness. In effect, the task (discussion) directs student attention to understanding through reasoning, providing a context for their learning (Tomanek and Montplaisir, 2004). When Dallimore and colleagues investigated individual random call, they showed that a greater number and variety of students volunteered to answer questions after random call became part of the classroom culture than when the only mechanism of calling on students was through asking them to volunteer.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, a task is demonstrated to be important with a reward of in-class validation, emphasizing the learning process and the value of sharing scientific ideas rather than correctness. In effect, the task (discussion) directs student attention to understanding through reasoning, providing a context for their learning (Tomanek and Montplaisir, 2004). When Dallimore and colleagues investigated individual random call, they showed that a greater number and variety of students volunteered to answer questions after random call became part of the classroom culture than when the only mechanism of calling on students was through asking them to volunteer.…”
Section: Introductionmentioning
confidence: 99%
“…The instructors of these classes generally expect students to learn the material and study for exams predominantly outside of the classroom with little direct guidance from the instructor. Since it is typical for grades in these large lecture courses to be based largely on exam scores, this likely encourages students to focus their efforts for learning the course material to prepare for exams (Tomanek & Montplaisir, 2004).…”
mentioning
confidence: 99%
“…A study by Tomanek and Montplaisir (2004) used this approach. In this study, the authors examined the study habits of students enrolled in a large introductory biology class.…”
Section: Concurrent Nested Designmentioning
confidence: 99%